COMIC LEARNING MEDIA DEVELOPMENT IN EFFORTS TO GROW LITERACY CULTURE AND ENVIRONMENTAL CARE ATTITUDE FOR ELEMENTARY SCHOOL STUDENT - Syifa' Lana; Rifqi Aulia Rahman; Rudi Danang Widodo (Universitas Sebelas Maret, 2018)
This research was aimed to describe the science comic design with the environmental care theme as a learning medium for developing the literacy culture and environmental care attitude for elementary school students. Research and Development (R & D) approach was implemented by utilizing 4D models which was limited to the Develop stage only. The comic media was reviewed and assessed by an expert of media, a linguist, an expert of material, and three elementary school teachers.. The data were collected by using observation technique and questionnaire. The results showed that the comic science media with the theme of environmental care can be used as a learning medium that can develop a culture of literacy and attitudes of environmental care in primary schools based on the contents of the curriculum standard 2013. The quality result of the assessment from the expert and the student response indicated a good category.